Development of an evidence-informed governance and stewardship framework for elderly healthcare in Iran: A qualitative study - Peivand Bastani; Jamshid Bahmaei; Ramin Ravangard; Mohammad Amin Bahrami; Abdolrahim Asadallahi; Reece Hinchcliff; Ingy Shafei (Heliyon, 2024)
Background: The ageing population poses significant challenges to healthcare systems, necessitating the establishment of high-functioning, integrated frameworks for elderly healthcare. This study aimed to explore the key challenges associated with the stewardship of elderly care in Iran and to develop a holistic stewardship framework. Methods: For this qualitative study, thirty semi-structured interviews were conducted with key Iranian healthcare stakeholders, utilizing purposive and snowball sampling during 2021–2022. Inductive open coding was utilized to generate new concepts related to key stewardship challenges. The World Health Organization's conceptual framework, outlining the three stewardship tasks, served as the basis for crafting a tailored framework for elderly healthcare stewardship in Iran. Results: Fourteen main challenges and 38 sub-challenges were identified for elderly healthcare stewardship in Iran, categorized according to the WHO framework's three stewardship tasks. Challenges related to WHO stewardship task 1, involving health policy formulation and vision definition, included challenges in vision definition, planning, policymaking, and intergovernmental institutional superiority. Challenges related to WHO stewardship task 2, delineating governance and stewardship through control and regulation, encompassed issues such as support for the elderly, system responsiveness, behavior of healthcare providers, organizational structure, and cross-sectoral leadership challenges. Challenges associated with WHO stewardship task 3, about the use of collective intelligence, explored stakeholder collaboration, information for decision-making, and challenges within the elderly information system, covering data documentation, reporting, analysis, accessibility, distribution, and circulation. Subsequently, a framework was developed, covering areas like defining the vision and direction of health policy, managing information systems, evidence-informed policymaking, and delivering elderly health services with a holistic approach. Conclusion: The present framework shows how a management information system, guided by evidenced-informed policymaking and the formulation of customized health policies, can facilitate the provision of elderly health services based on identified needs. It presents a governance and stewardship pathway that can be adopted by Iranian health policymakers and similar middle-income countries facing analogous challenges in ageing and aged care system stewardship, serving as a model for developing their own frameworks.